Estudo fitoquímico e ensaios biológicos de Davilla Kunthii A. St. -Hil (Dilleniaceae) - Nascimento, Leandro da Silva (2014)
The use of plants or plant extracts for medicinal purposes has been done for thousands of years. The chemical and biological study of plants is an alternative strategy in the search for new therapeutic agents for the identification of bioactive compounds. The Davilla kunthii A. St.-Hil species belonging to Dilleniaceae family, is popularly known as vine-of-fire and can be found in savanna regions. This work aimed to make the phytochemical study and biological assays of the species Davilla kunthii A. St.-Hil, considering that to date regarding chemical and biological records of this species were not found. The species was collected in the Campus Center Cauamé Agricultural Sciences, Federal University of Roraima (CCA / UFRR). For the preparation of hexane and ethanol extracts of the leaves of D. kunthii A. St.-Hil plant materials were placed in glass mariotes for cold extraction in n-hexane and then ethanol. The ethanol extract of the leaves, which after partitioned, yielded fractions in hexane, chloroform, ethyl acetate and methanol. The fractions of the chloroform extract were purified and analyzed by chromatographic methods. The compounds were identified by spectroscopic techniques and compared with literature data. The phytochemical study of leaves led to the isolation and identification of a mixture of fatty acids as their methyl esters (determined by GC), a mixture of β-sitosterol and stigmasterol and alcohol Triacontan-1-ol (Alcohol Melíssilico). In biological assays leaves extract showed a MIC (Minimum Inhibitory Concentration) variation from 6.2 to 53.7% for S. aureus and S. sanguinis bacteria. As for the E. coli bacteria and S. tiphymurium the MIC ranged from 9.23 to 38.2% and the yeast C. albicans MIC was 92.5 to 95.3%. It is concluded that the ethanol extract of the leaves of D. kunthii A. St.-Hil showed low toxicity on Artemia salina, an excellent activity against the yeast C. albicans as well as revealing a great antioxidant capacity of the species by the method of reduction the DPPH radical. However, they were not reported on the species is expected that these results will contribute to the phytochemical study of this plant family.